A numerical study on the fatigue life design of concrete slabs for railway tracks. (1st October 2015) - Poveda, Elisa; Yu, Rena C.; Lancha, Juan C.; Ruiz, Gonzalo
Highlights: Dynamic analysis for a three-slab track system. Validation of fatigue model for railway slabs against full-scale tests. A new fatigue damage criterion proper of concrete-like materials. Novel signal processing to obtain the worst train pulses for a desired reliability value. Optimisation of slab geometry and material strength for fatigue design. Abstract: With the growing use of high-speed trains, non-ballasted tracks have become more popular compared to ballasted ones. However, the study on fatigue evaluation in concrete slabs under train load has been rather limited. This work presents a numerical study on the fatigue life design of concrete slabs for railway tracks. A finite element model for a three-slab track system is established for extracting the principal vibration modes and transient analysis under time-dependent loads. The fatigue evaluation procedure is first validated against full-scale experiments on slabs carried out in a three-point-bend load configuration under fatigue. Next, techniques in the context of digital signal processing, i.e., random phases combined with each constituent frequency amplitude to generate new load pulses, are employed to obtain the most unfavourable load scenario from numerous measured real-time train loads. A novel fatigue criterion which singles out the significance of stress amplitude (proper to concrete-like materials) is implemented to obtain the critical load direction. Fatigue damage under compression is evaluated under this most unfavourable load situation. Meanwhile, parametric analyses on material strength and slab geometry are carried out, recommendations for improved designs towards fatigue life are given accordingly. Even though the established procedure is demonstrated for fatigue under compression, damage evaluation based on the Model Code, extension to tension or mixed tension–compressive stress evaluations, as well as damage calculations with alternative criterions can be easily implemented.